Validation of a Spanish version of the Spine Functional Index - Cuesta-Vargas, Antonio; Gabel, Charles Philips (BMC Springer Nature, 2014)
Background: The Spine Functional Index (SFI) is a recently published, robust and clinimetrically valid patient reported outcome measure. Objectives: The purpose of this study was the adaptation and validation of a Spanish-version (SFI-Sp) with cultural and linguistic equivalence. Methods: A two stage observational study was conducted. The SFI was cross-culturally adapted to Spanish through double forward and backward translation then validated for its psychometric characteristics. Participants (n = 226) with various spine conditions of >12 weeks duration completed the SFI-Sp and a region specific measure: for the back, the Roland Morris Questionnaire (RMQ) and Backache Index (BADIX); for the neck, the Neck Disability Index (NDI); for general health the EQ-5D and SF-12. The full sample was employed to determine internal consistency, concurrent criterion validity by region and health, construct validity and factor structure. A subgroup (n = 51) was used to determine reliability at seven days. Results: The SFI-Sp demonstrated high internal consistency (α = 0.85) and reliability (r = 0.96). The factor structure was one-dimensional and supported construct validity. Criterion specific validity for function was high with the RMQ (r = 0.79), moderate with the BADIX (r = 0.59) and low with the NDI (r = 0.46). For general health it was low with the EQ-5D and inversely correlated (r = -0.42) and fair with the Physical and Mental Components of the SF-12 and inversely correlated (r = -0.56 and r = -0.48), respectively. The study limitations included the lack of longitudinal data regarding other psychometric properties, specifically responsiveness. Conclusions: The SFI-Sp was demonstrated as a valid and reliable spine-regional outcome measure. The psychometric properties were comparable to and supported those of the English-version, however further longitudinal investigations are required.
Keywords: Columna vertebral - Test; Spine; Psychometrics; Outcome measure; Spanish